The Effect of Job Insecurity and Workload on Turnover Intention of Employees of PT Saka Farma Laboratories - Eka Yudhyani; Zilfana Zilfana; Alona Shaikha Dianova Syahrani (Poltanesa, 2025)
One of the factors that cause turnover intention is job insecurity, where job insecurity is the emergence of feelings of insecurity to threats related to work. In addition, workload is also one of the factors that cause turnover intention. The purpose of this study is to determine and analyze the effect of job insecurity and workload partially and simultaneously on the turnover intention of employees of PT Saka Farma Laboratories. Primary data in this study were obtained from interviews and questionnaires filled out by respondents and observations made by researchers. The population in this study were 100 employees who worked at PT Saka Farma Laboratories and the number of samples used in this study were 60 respondents. The sampling technique used was purposive sampling. The analytical tool used is multiple linear regression using SPSS 30. The results of this study indicate that job insecurity has a positive and significant effect on turnover intention of PT Saka Farma Laboratories employees. Workload does not significantly affect the turnover intention of PT Saka Farma Laboratories employees. Job insecurity and workload variables together have a positive and significant effect on employee turnover intention of PT Saka Farma Laboratories.